Construction and Development Strategy of an Application System of Intelligent Sports in China’s Sports Industry - Tang, Yuxin; Zan, Shengfeng; Zhang, Xiaowen; Zhu, Wenyan (Mathematical problems in engineering, 2022)
Methods of literature review and model construction were used to study the construction and development strategy of an intelligent sports application system in the sports industry. After the literature review of the sports industry and the application of artificial intelligence in this industry, we analyzed the significance of the intelligent sports application system for the development of the Chinese sports industry from the perspective of elements, data, and policies in the sports industry. The research followed four principles of system construction, which are scientificity, practicalness, efficiency, and coordination. First, we built a framework for the intelligent sports application system and designed its function from governmental, industrial, political, and individual perspectives. Second, the content of the application system was analyzed in detailed in five layers including technology, industry, application, challenge, and security. Finally, we structured the operation model according to four units: the database, intermediary platform, social subjects, and industrial subjects. This study put forward the following policy implication: it is required to (1) improve the top-level design of intelligent sports, (2) optimize the intelligent sports market environment, (3) innovate and upgrade the intelligent sports industry, and (4) build an intelligent sports talent system.